2018
DOI: 10.1186/s12879-018-3462-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic factors associated with increased risk of severe liver toxicity in a monocentric cohort of HIV positive patients receiving nevirapine-based antiretroviral therapy

Abstract: BackgroundNevirapine has been used as antiretroviral agent since early ‘90. Although nevirapine is not currently recommended in initial anti-HIV regimens, its use remains consistent in a certain number of HIV-1-positive subjects. Thus, our aim was to determine clinical and genetic factors involved in the development of severe nevirapine induced liver toxicity.MethodsWe retrospectively analyzed all HIV positive patients who were followed at the Infectious Diseases Unit, DIBIC Luigi Sacco, University of Milan fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…In our study, many more femalesdevelopedhepatotoxicitywhen compared with males (Table 1).Our findings are similar to those of studiesreported in Fako-Cameroon [29,30], elsewhere in Ethiopia [15,31,33] and in Milan-Italy [21].However, studies in Zürich-Switzerland [37], Tanzania [36] and Ethiopia [23], reported higher rates of hepatotoxicity amongmale than female patients on cART.…”
Section: General Characteristicssupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, many more femalesdevelopedhepatotoxicitywhen compared with males (Table 1).Our findings are similar to those of studiesreported in Fako-Cameroon [29,30], elsewhere in Ethiopia [15,31,33] and in Milan-Italy [21].However, studies in Zürich-Switzerland [37], Tanzania [36] and Ethiopia [23], reported higher rates of hepatotoxicity amongmale than female patients on cART.…”
Section: General Characteristicssupporting
confidence: 91%
“…Highly Active Anti-Retroviral Therapy (HAART)-associated hepatoxicity/ cART-induced hepatotoxicity (CIH), arbitrarily defined as AST or ALT > 3 X upper limit of normal (ULN) in the presence of symptoms, or serum AST or ALT > 5 X ULN in the absence of symptoms, usually resolves without modification of therapy [13][14][15][16][17][18]. Hepatotoxicity, which is the most cited reason for the withdrawal of approved drugs, is damage caused by exposure to a drug or non-pharmacological agents [19],and is consequently associated with HAART/ cART [15,20] especially nevirapine-based HAART [21] or efavirenz-based drug-induced liver injury [22]. In isolated instances, serious and life-threatening conditions may arise.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Active Anti-Retroviral Therapy (HAART)-associated hepatoxicity/ cART-induced hepatotoxicity (CIH), arbitrarily defined as AST or ALT > 3 X upper limit of normal (ULN) in the presence of symptoms, or serum AST or ALT > 5 X ULN in the absence of symptoms, usually resolves without modification of therapy [13][14][15][16][17][18]. Hepatotoxicity, which is the most cited reason for the withdrawal of approved drugs, is damage caused by exposure to a drug or nonpharmacological agents [19],and is consequently associated with HAART/ cART [15,20] especially nevirapine-based HAART [21] or efavirenz-based drug-induced liver injury [22]. In isolated instances, serious and life-threatening conditions may arise.…”
Section: Highlymentioning
confidence: 99%
“…The non-nucleoside reverse transcriptases inhibitors (NNRTI) typically cause either hypersensitivity reactions or direct drug toxicity and therefore have two peaks of onset: within days to weeks or several months after initiation [25]. Nevirapine (NVP) is the NNRTI most associated with hepatotoxicity [21], though hypersensitivity reactions resulting in liver failure have been reported with the newer NNRTI etravirine. Efavirenz and stavudine can also cause hepatotoxicity but does so less frequently than NVP or etravirine [22].…”
Section: Highlymentioning
confidence: 99%